2021
DOI: 10.1111/eea.13102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on host plant‐specific leaf‐ and root‐feeding performances: a comparison of grape phylloxera biotypes C and G

Abstract: Grape phylloxera, Daktulosphaira vitifoliae (Fitch) (Hemiptera: Phylloxeridae), is a destructive pest for global viticulture. With the grafting of the susceptible cultivated grapevine (Vitis vinifera L., Vitaceae) on top of tolerant Vitis spp. rootstock, root infestation no longer causes vine death. These tolerant rootstock vines are hybrids of American species that are often highly susceptible to leaf infestation. Though leaf infestation is normally rarely seen on V. vinifera, some commercial vineyards have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…A high external infestation pressure from leaf-feeding phylloxera on nearby susceptible Vitis species can explain the results of some of these studies. Infestation assays under controlled conditions, however, showed that some phylloxera populations from this study area have a significantly higher rate of infestation and faster development on V. vinifera leaves compared to less adapted phylloxera populations (Wilmink et al, 2021a). Instead of temporal and marginal foliar outbreaks, some commercial vineyards in Baden, Germany, were subjected to vineyard-wide leaf infestations perpetuated throughout the growing season.…”
Section: Introductionmentioning
confidence: 74%
“…A high external infestation pressure from leaf-feeding phylloxera on nearby susceptible Vitis species can explain the results of some of these studies. Infestation assays under controlled conditions, however, showed that some phylloxera populations from this study area have a significantly higher rate of infestation and faster development on V. vinifera leaves compared to less adapted phylloxera populations (Wilmink et al, 2021a). Instead of temporal and marginal foliar outbreaks, some commercial vineyards in Baden, Germany, were subjected to vineyard-wide leaf infestations perpetuated throughout the growing season.…”
Section: Introductionmentioning
confidence: 74%